KONSEP QATH’I DAN ZHANNI AL-DALALAH DAN PENGARUHNYA TERHADAP PENAFSIRAN AL-QUR’AN - Firdaus, Firdaus (DIKTUM: Jurnal Syariah dan Hukum, 2013)
This article describes the problem and the concept qath'i zhanni al-dalalah and its influence on the interpretation of the Qur'an. From the results obtained literatus assessment some understanding that the Qur'an as the word of Allah, there is no difference of opinion among Muslims regarding the truth of the source, ie from Allah. Muslims also have the same belief that the editorial verses of the Qur'an were collected in the manuscripts is the same without the slightest difference to that received by the Prophet Muhammad. Of Allah. through the Angel Gabriel. Layout differences among Muslims is in terms of editorial content of the meaning of the verses of the Qur'an. Usul Fiqh Scholars divide the texts of the Qur'an to the two components, namely qath'i and zhanni al-dalalah. Qath'i al-dalalah is clear and certain passages that have only one meaning, and not open to other meanings. While al-dalalah zhanni is the opposite of qath'i al-dalalah, he was open to interpretation. Another interpretation by scholars, he did not make the classification of passages of the Qur'an, that there is no one zhanni qath'i and al-dalalah, because he thinks in that way it was meant to limit the meaning, and interpretation al-Qur 'an. In the Qur'an it is able to contain a lot of interpretation. With the concept of al-dalalah qath'i by scholars Usul Fiqh course is unfavorable interpretations among scholars, because the concept was meant to limit the meaning efforts, interpretation of the texts of the Qur'an itself. But the concept of al-dalalah zhanni by Ulama Usul Fiqh, wide open opportunities to interpret, interpret the texts of the Qur'an was, in a sense have a major impact and positive influence on the birth of the commentators and the mujtahid.